Assessment of Multicolor Flow Cytometry Panels to Study Leukocyte Subset Alterations in Water Buffalo (Bubalus bubalis) During BVDV Acute Infection - Grandoni, Francesco; Martucciello, Alessandra; Petrini, Stefano; Steri, Roberto; Donniacuo, Anna; Casciari, Cristina; Scatà, Maria Carmela; Grassi, Carlo; Vecchio, Domenico; Feliziani, Francesco; De Matteis, Giovanna; Davis, William C.; et al. (Frontiers in Veterinary Science, 2020)
The identification of cross-reactive monoclonal antibodies (mAbs) that recognize orthologous leukocyte differentiation molecules (LDM) in buffaloes has overcome a major impediment limiting research on the immune response to pathogens and development of vaccines. As reported, studies were conducted to accomplish two objectives: 1) demonstrate that multiparameter flow cytometry can be conducted equally well with mAbs directly and indirectly labeled with fluorochromes in research and 2) flow cytometry can be used to compare and extend studies on diseases of economic importance to buffalo using bovine viral diarrhoea virus (BVDV) as a model pathogen. Pregnant buffalo cows were infected with BVDV-1 at 81 (trial-1) and 203 (trial-2) days post artificial insemination and followed daily for a month and then every 3 days thereafter. Fluorochrome conjugated mAbs were used in trial 1. Fluorochrome conjugated goat isotype specific anti-mouse antibodies were used to label mAbs in trial 2. No difference was observed in the use of mAbs directly or indirectly labeled with fluorochromes to analyze the composition of leukocyte subsets. Flow cytometric analysis revealed a transient lymphopenia occurs during the first days following infection similar to lymphopenia reported in cattle. No differences were observed in the frequency of monocytes or neutrophils. No clinical signs of infection were observed during the evaluation period of buffaloes experimentally infected with BVDV, however, animals in trial-1 developed complications later in the course of the infection. One cow aborted at 57 days post-infection. The second cow developed a prolapse a day after calving and died